Stages of Development and Metamorphosis of Tree Frog Rhacophorus Bipunctatus (Amphibia, Anura, Rhacophoridae) - Iangrai, A. J.; Hooroo, R. N. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Amphibians are the highest vertebrate group to retain an essentially naked egg and the only vertebrate group which has an aquatic larval stage and a terrestrial adult phase. One of the prominent life history characteristics common to most living amphibians is the presence of an aquatic larval period, which immediately follows the initial embryonic development after fertilization and ends with the completion of metamorphosis. Metamorphosis in anurans involves resorption of the tail, development of the front and hind limbs and large changes in most organ system. Proper staging of the larval period is therefore necessary for accurate comparison of developmental stages in different organisms. Hence, several workers [1-3] have reported on tables of normal stages of development for a number of species. Keeping in view the paucity of information on the development and metamorphosis of tree frogs from Meghalaya, it was decided to study the development and metamorphosis of the tree frog Rhacophorus bipunctatus at Cherrepunjee, Meghalaya. The present study was conducted during the breeding season (April to August). In the present study it was found that, the development and metamorphosis of Rhacophorus bipunctatus was completed in about 59 – 60 days under natural environment as well as in the laboratory condition. This tree frog was observed to be dependent on the rain fed pools at the breeding sites to complete their life cycle.